'I'm good, but not that good': digitally-skilled young people's identity in computing. Issue 4 (8th December 2016) - Wong, Billy
Abstract: Computers and information technology are fast becoming a part of young people's everyday life. However, there remains a difference between the majority who can use computers and the minority who are computer scientists or professionals. Drawing on 32 semi-structured interviews with digitally skilled young people (aged 13–19), we explore their views and aspirations in computing, with a focus on the identities and discourses that these youngsters articulate in relation to this field. Our findings suggest that, even among digitally skilled young people, traditional identities of computing as people who are clever but antisocial still prevail, which can be unattractive for youths, especially girls. Digitally skilled youths identify with computing in different ways and for different reasons. Most enjoy doing computing but few aspired to being a computer person. Implications of our findings for computing education are discussed especially the continued need to broaden identities in computing, even for the digitally skilled.